Tool-Use Training Induces Changes of the Body Schema in the Limb Without Using Tool - Sun, Yu; Tang, Rixin (Frontiers in Human Neuroscience, 2019)
Previous studies have shown that tool use affects the plasticity of the body schema. In other words, people will perceive the tool as a part of their body, and thus feel like they have “longer limbs” after using tools. However, it is unclear whether tool embodiment could spread to a limb that is not using the tool, and whether other limbs could utilize the proprioception of a limb. In Experiment 1, blindfolded participants were asked to search with a cane (Condition 1) or to walk with a cane (Condition 2). The results in Condition 1 illustrated that the tactile distance perception on the forearm was lengthened after tool use, while other body parts did not significantly change. In Condition 2, the tactile distance perception on the hand and forearm extended significantly after using tools. Additionally, tool-use training even induced an increased perception of the calf that was not using the tool. Possible interference from the difference between walking and standing was excluded in Experiment 2. These results demonstrate that the proprioception information of one limb could be exploited by another limb to extend the body schema even though that limb was not using a tool. It was also observed that the effect of direction was task-dependent in the tactile perception task.